A concurrent engineering approach for business collaboration: a case in the toy industry. (1st January 2003) - Pun, K.F.; Yam, R.C.M.; Sun, H.; Leung, K.Y.
Today's manufacturers are looking for competitive advantages of cost, quality, safety, time and creativity. Concurrent engineering (CE) stresses cross-functional integration and simultaneous development of a product and its associated processes. It offers the potential for development of quality producible products, and helps firms foster business collaboration with strategic partners. This paper discusses the adoption of a CE approach for revitalising sequential operational practices in the toy industry. A trial implementation of an Integrated Concurrent Engineering System (ICES) is presented based on a collaboration case study of three toy companies for performance improvements. The concurrent operation practices and product development strategies are explained. The ICES was proven a feasible option for companies attempting sustainable collaboration operations in today's competitive marketplace.